Годишњак бр. 23 (2024) Hybris ethos-a? Прилог o патосном и респонзивном карактеру српскозаветног идентитета - Вук Беговић (Godišnjak)
Only if the contours of diastatic spaced experience (both worldly and life-configured, as well as metaphorical and poetical) were spectrally expanded by an infinite imaginary space would the Serbian-covenantal experience gain integratively more fruitful and deeper, and thus different, possibilities of living the (Serbian) covenant. Hence, this contribution hints at a phenomenologically redirected (Orthodox) theology and hermeneutics of the covenant, rather than merely existential-ontologically enforced wishes. Theologically, this represents the covenantal Christophany as the Christoprismaticity of Theophany. Contemporary (critical) phenomenology, which is both medial and responsive, offers a hermeneutics of difference as primarily a dialogical, communicable, and resonant space, creating conditions for a much denser (germ. dicht) elaboration and self-critical stimulation of responsible historico-theological thinking, speaking, and acting.In the following article, it is therefore suggested to shift the diacritical focus from ethos, that is, from the hermeneutic coupling of (onto-)logos and ethos, to the third and contingently forcing figure of pathos, which affectively destabilizes the universal demand for a fundamentally ontologizing petrification of ethos – as an ultimately perceived solution and thus in the role of overlooking the complexity, problematicity, and potency of the Serbian vow phenomenon – by making the pathic figuration of pronounced identity, integrative, and sovereigntist claims paradoxically more flexible and stable through denser differentiation. More integrative. Thus, such a differentially valid hermeneutics in the theological horizon could profile an ethics of decision-making that would not generate either inclusive or exclusive moments of responsibility, but rather, not infrequently and potentially more frequently, non-indifferently skilled in discernment, ready to avoid abrupt and restructured responses. More precisely, it aims not only to decisively (not) decide, but also to be more circumspect and as sensitively nuanced as possible in discerning the subtleties of each inter-decision.